Are Plasma Thyroid-Stimulating Hormone Levels Associated with Degree of Obesity and Metabolic Syndrome in Euthyroid Obese Patients? A Turkish Cohort Study. (2nd January 2014) - Bakiner, Okan; Bozkirli, Emre; Cavlak, Gulhan; Ozsahin, Kursad; Ertorer, Eda
Abstract : We aimed to observe the association between degree of obesity and metabolic syndrome and plasma thyrotropin levels in obese, euthyroid Turkish patients. 947 obese and overweight patients who admitted to our outpatient clinic were assessed retrospectively. 150 healthy euthyroid cases were also recruited as the control group. Cases with metabolic syndrome were determined. Patients were divided into various subgroups as overweight, obese, morbid obese, men, and women. No statistical significance was determined when all the patients' and subgroups' plasma thyrotropin levels were compared to normal weight control group. No association was shown between the presence of metabolic syndrome and plasma thyrotropin levels for both all patients and subgroups. Also there was not any association between each component of metabolic syndrome and plasma thyrotropin levels. In conclusion, we did not found any significant association between plasma thyrotropin levels and obesity and metabolic syndrome in our euthyroid subjects.